O Estado do conhecimento sobre os cuidadores escolares de crianças autistas no ensino regular e suas práticas educativas - CONDE, Larissa Fernanda Alves (2021)
This article aims to raise and analyze productions that deal with caregivers of autistic children in Graduate Programs in Brazil in the area of Education between 2014 and 2019. The survey was conducted on the platforms: Catalog of Theses and Dissertations of the Coordination of Improvement Higher Education Personnel (CAPES), the CAPES Journals Portal and Google Scholar. First, the productions with the keyword school caregiver were raised and then school caregiver and autism. The results indicated a small production in the studies on school caregivers of children with ASD. Five productions were found that focused on two categories: (a) School Caregiver and Autism; (b) School Caregiver. It is considered the need to expand research on the theme addressed.